Estimation of Organ Dose, Effective Dose, and Cancer Risk in Abdominal CT Scan Patients - Putri, S. S.; Intifadhah, S. H.; Putri, E. R. (National Research and Innovation Agency, 2024)
Computed tomography scan (CT scan) is a modality that is used to diagnose diseases inside the human body. In the scanning process, the patient will receive radiation from the CT scanner, so that it is necessary to calculate the amount of radiation dose. The purpose of this study was to determine the organ dose, effective dose, and cancer risk received by abdominal examination patients. Data taken from the results of abdominal examination patients at Radiology Installation of A.W. Sjahranie Regional Hospital Samarinda using 16-slice CT scan modality GE BRIVO type D3161T. The data collected included 150 patients, both female and male, with ages ranging from 15 to 79 years. Dosimetry parameters taken from CT scan results are the exposure factor (kV, mAs), scan length, computed tomography dosimetry indeks volume (CTDIvol), and dose length product (DLP) of the patient. CTDIvol and DLP of the patient are used to calculate the organ dose, effective dose, and cancer risk values of abdominal CT scan patients. Then the effective dose value received by the abdominal CT scan examination patient is compared with the Nuclear Energy Regulatory Agency of Indonesia (BAPETEN) standard based on the CTDIvol and DLP values of the patient, and also compared with the International Commission Radiological Protection (ICRP) standard. Based on the results of organ dose estimation calculations, the average value of the stomach is 0.82 mSv, the gonads are 0.54 mSv, and the bladder is 0.28 mSv. Meanwhile, the average value of effective dose received by abdominal examination patients is 5.28 mSv with an average cancer risk of 0.029 %. Based on the CTDIvol and DLP values of the patients, the 3rd quartile values of the patients were 8.25 mGy and 413.84 mGy.cm. This value is still below the value recommended by BAPETEN when viewed from the 2021 Diagnostic Reference Level (DRL) guidelines. The effective dose received by one patient exceeded the standard set by the ICRP. Meanwhile, the cancer risk received by patients is still in a low percentage.